2008
DOI: 10.1057/palgrave.jibs.8400422
|View full text |Cite
|
Sign up to set email alerts
|

Guanxi vs networking: Distinctive configurations of affect- and cognition-based trust in the networks of Chinese vs American managers

Abstract: This research investigates hypotheses about differences between Chinese and American managers in the configuration of trusting relationships within their professional networks. Consistent with hypotheses about Chinese familial collectivism, an egocentric network survey found that affect- and cognition-based trust were more intertwined for Chinese than for American managers. In addition, the effect of economic exchange on affect-based trust was more positive for Chinese than for Americans, whereas the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
249
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(255 citation statements)
references
References 55 publications
3
249
1
2
Order By: Relevance
“…Leung et al (2008) suggest that expatriates doing business in China need to transfer themselves from strangers into in-group of their Chinese counterparts. Chua et al (2009) found that the indirect social ties appear to have a bigger role for Chinese than for American managers. Consider the case discussed above, in which A in the ABC Company received Renqing form A's classmate, B, in the XYZ Company.…”
Section: Resultsmentioning
confidence: 93%
“…Leung et al (2008) suggest that expatriates doing business in China need to transfer themselves from strangers into in-group of their Chinese counterparts. Chua et al (2009) found that the indirect social ties appear to have a bigger role for Chinese than for American managers. Consider the case discussed above, in which A in the ABC Company received Renqing form A's classmate, B, in the XYZ Company.…”
Section: Resultsmentioning
confidence: 93%
“…Equally, it is the socio-cultural reality that guanxi is the modus operandi in traditional Chinese business practices. Within this, as recent research on trust in Chinese and American business practice has suggested (Chua and Morris, 2006;Chua et al, 2009), Chinese managers actually have more kin (family members) in their professional networks. In other words, guanxi is not just an extension of familial collectivism to business settings, it is also based on interaction with family members.…”
Section: The Role Of Guanxi Connections As a Culturally Specific Formmentioning
confidence: 98%
“…We argue that it is critical in this context to understand the role of guanxi as it impacts upon women in the labour market (Yueh, 2006) and the nature of gender as a construct and its reality in the society and culture of China (Zheng, 2003). Paralleling the importance of familial collectivism (Chua et al, 2009;Bond and Hwang, 1986;Yang, 1988;Redding and Wong, 1986) in Chinese society, it has been argued that guanxi mirrors this in social and, especially, business relationships: in effect, guanxi is "an extension of family norms to business settings" (Chua et al, 2009, 502). Furthermore, Chen and Chen (2004, p. 308) highlighted a typology (as with social capital -bridging, bonding, etc.…”
Section: The Role Of Guanxi Connections As a Culturally Specific Formmentioning
confidence: 99%
“…From the perspective of strategic management, guanxi is often regarded as a particular and inimitable strategic resource that can help firms develop and maintain their competitive advantage [19][20][21]. As mentioned earlier, guanxi reflects the Chinese contextual notion and the way that people can do business more effectively and successfully.…”
Section: Guanxi Strategy Theorymentioning
confidence: 99%